Նոր քաղաք-Կայնեպոլիս-Վաղարշապատ - Ժորես Խաչատրյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
У части арменоведов бытует мнение, что город Валаршапат основал Валарш I (117-140/143 гг.) и перенес туда царский двор. According to the version of a group of Armenologists the town of Valarshapat was founded by Valarsh I (117-140/143) and the capital of Armenia was removed here.
Keywords: History; Ancient History